Study the Effect of Perforation Type for Plate with Central Crack on the Stress Intensity Factor Using the XFEM - Mashjel, Ahmed Obaid; Laftah, Rafil Mahmood; Khalaf, Hassanein Ibraheem (Basrah Journal for Engineering Sciences, 2021)
In this study, loading was carried out for several types of perforated plates, such as circular, rhombic and rectangular holes, where the holes were arranged in two types, namely straight arrangement and alternating arrangement. The stress intensity factor and shape factor were calculated for each case, taking into account the diameter of the holes. So, it is found the SIF increases significantly when the plate is perforated, and the same applies to the shape factor, also increases. In the case of circular holes, the increases in the average value of (SIF) reached to (80.88 %) when the plate was perforated with alternated arranged of circular holes, while the straight arrangement of circular holes the increases of average values of SIF reach to (67.55 %). Either in the case of rhombus holes: the SIF values are increases to (51.07 %) when the plate was perforated with the alternated arrangement, while in the straight arrangement of holes the (SIF) increase to (35.43 %). It was observed through this study, the increases of stress intensity factor and the shape factor with different crack lengths were more stable in the plate that perforated with an alternated arrangement of holes than the straight arrangement. The higher values of stress intensity factor obtained when the plates were perforated with circular holes, due to the circular shape has more stiffness, so the Absorption of force will be small Compared with the rhombus and rectangular shape that will be less stiffness which the absorption of strength is greater.